The Zmijewski Model as an Early Indicator of Financial Distress in Retail Companies Listed on the Indonesia Stock Exchange - Deni Surya Alam; Ali Mugayat; Mery Sukartini (Studi Ilmu Manajemen dan Organisasi, 2026)
Purpose: This study aims to evaluate the effectiveness of the Zmijewski Model as an early warning tool for detecting financial distress in retail companies listed on the Indonesia Stock Exchange. Methodology/approach: The research focuses on 7 companies in the food and staples retailing subsector, using the Zmijewski Model developed in 1984, which includes three financial ratios: current ratio (CR), debt to equity ratio (DER), and return on assets (ROA). The analysis uses annual financial statements, applying a descriptive quantitative approach to calculate and interpret the X-scores. Results/Findings: The results indicate that the Zmijewski Model accurately predicts financial distress. Companies with positive X-scores are at higher risk of financial problems, while those with positive scores are considered stable. Conclusions: The Zmijewski Model proves to be an effective tool in identifying early signs of financial distress using basic financial ratios, aiding managers and investors in making better financial decisions. Limitations: The model does not account for external factors such as market conditions or economic crises, which could impact a company’s financial stability. Contribution: This study contributes to financial management and accounting by demonstrating how a simple model can be utilized to detect financial distress early, benefiting investors, company managers, auditors, and researchers in the field.